Revisiting cartography: towards identifying and developing a modern and comprehensive framework - Basaraner, Melih (TAYLOR & FRANCIS LTD, 2016)
Developments in production, sharing and use of spatial data and information involve revisiting the role and scope of cartography. Cartography is a core discipline for spatially modelling, investigating and mapping natural and cultural environments, developing location-aware applications, establishing spatial data infrastructures and forming spatially enabled societies. In this context, spatial data handling provides key tools for creating spatial databases, integrating spatial data, producing geographic information and maps and so on. Although cartography plays a key role in many phases of such activities, it tends to be introduced only as visualization phase of spatial data handling. On the other hand, it is sometimes regarded to encompass entire phases of spatial data handling. So this article investigates the relationships between cartography and spatial data handling, management and use, and on this basis, proposes a modern and comprehensive framework for cartography to contribute to restoring the full conceptual breadth of the discipline.
Keywords: cartography; spatial data handling; management and use; spatial data infrastructure; spatially enabled society; GIScience; RESEARCH AGENDA; Environmental Sciences & Ecology; Geology; Remote Sensing; Imaging Science & Photographic Technology